Contribution to hair and skin science in Indonesia through a research grant program - Verschoore, Michele; setiawan, rhadeya; Listiawan, Muhammad Yulianto; Nurtami, Nurtami; Moreau de Montcheuil, Eloïse (UI Scholars Hub, 2024)
To foster scientific advances in basic and clinical research projects, a philanthropic